Marketing experimental: análise de conteúdo na indústria automobilística - Paes, Gabriel Barbosa [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The screen work seeks to illustrate the experiential marketing strategies, relating these concepts within the automotive industry. From the methodology of content analysis, success stories of the automotive industry have been analyzed in the light of experimental marketing theories to elucidate the strategies of organizations with their target audience. The objectives aimed at understanding and studying experiential marketing within the market scenario, identify its main characteristics and applicability. The main results stand out that sensory experiences provided by experiential marketing can be the differentiating factors between organizations, especially, those of the automotive sector

O trabalho em tela busca ilustrar as estratégias de marketing experimental, relacionando esses conceitos dentro da indústria automobilística. A partir da metodologia de análise de conteúdo, cases de sucesso da indústria automobilística foram analisados à luz das teorias marketing experimental, para elucidar as estratégias das organizações para com seu público alvo. Os objetivos visaram compreender e estudar o marketing experimental dentro do cenário mercadológico, identificar suas principais características e aplicabilidades. Como principais resultados destacam-se que as experiências sensoriais proporcionadas pelo marketing experimental podem ser fatores de diferenciação entre as organizações, com destaque, paras àquelas do setor automobilístico
Keywords: Indústria automobilística; Marketing; Experiencia; Automobile industry and trade